2015
DOI: 10.1038/srep11745
|View full text |Cite
|
Sign up to set email alerts
|

Multiple scale model for cell migration in monolayers: Elastic mismatch between cells enhances motility

Abstract: We propose a multiscale model for monolayer of motile cells that comprise normal and cancer cells. In the model, the two types of cells have identical properties except for their elasticity; cancer cells are softer and normal cells are stiffer. The goal is to isolate the role of elasticity mismatch on the migration potential of cancer cells in the absence of other contributions that are present in real cells. The methodology is based on a phase-field description where each cell is modeled as a highly-deformabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
110
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 47 publications
(75 reference statements)
1
110
0
Order By: Relevance
“…Its stochastic simulation included the effect of cell migration, compression, and contact inhibition to describe the evolution of cell size distribution and the global colony growth. Furthermore, a phase field cell monolayer model with its dynamics approaching the continuous limit of the Potts model has been used to describe the increase in the motility of cells softer than their neighbors, in agreement with experimental data from human metastatic breast carcinoma cells (MDA-MB-231) co-cultured with normal epithelial cells (MCF10A) [31]. In this case, carcinoma cells are softer than normal cells [32] and the mismatch in cell elasticity causes several speed "bursts" in which the cancer cell relaxes from a largely deformed shape and consequently, its translational motion increases.…”
Section: Introductionsupporting
confidence: 56%
“…Its stochastic simulation included the effect of cell migration, compression, and contact inhibition to describe the evolution of cell size distribution and the global colony growth. Furthermore, a phase field cell monolayer model with its dynamics approaching the continuous limit of the Potts model has been used to describe the increase in the motility of cells softer than their neighbors, in agreement with experimental data from human metastatic breast carcinoma cells (MDA-MB-231) co-cultured with normal epithelial cells (MCF10A) [31]. In this case, carcinoma cells are softer than normal cells [32] and the mismatch in cell elasticity causes several speed "bursts" in which the cancer cell relaxes from a largely deformed shape and consequently, its translational motion increases.…”
Section: Introductionsupporting
confidence: 56%
“…[151][152][153] It was able to reproduce many experimentally observed effects, including inelastic scattering of colliding cells and 'activation' of nonmotile cells by moving cells owing to steric interactions 153 and the emergence of coherently moving or rotating cell clusters, 152,153 as well as the formation of tissue-like stationary clusters. 151,153 Again, computational modelling produced a number of important insights, e.g., it was shown that-at least in a non-confluent situation-cell-cell adhesion rather hinders collective migration of cells, as it induces the formation of short-living clusters of only few cells. 153 This observation sheds light, for instance, on comparative studies of adhesive (healthy) cells versus weakly adhering (cancerous) cells.…”
Section: Future Directions and Outlookmentioning
confidence: 85%
“…153 This observation sheds light, for instance, on comparative studies of adhesive (healthy) cells versus weakly adhering (cancerous) cells. Currently, in all multicell approaches a separate phase field was assigned to each cell, [150][151][152][153] permitting with the present power of graphic processing units to simulate about a hundred cells. This approach, however, is computationally not yet optimized, as a substantial part of the computing time is spend on updating zeros (note that most fields are typically zero outside the cells).…”
Section: Future Directions and Outlookmentioning
confidence: 99%
See 2 more Smart Citations